Crisis response strategy and crisis types suitability: a preliminary study on MH370 - Mohamad Ashari, Noratikah; Abang Ahmad, Dayang Aizza Maisha; Samani, Mus Chairil (2017)
In time of crisis, the organisation’s tactic in responding to the crisis according to its type/s may significantly affect the organisation’s effort to survive its reputational damages.The study of crisis response strategy (CRS) requires further exploration within the Malaysian context, moreso with the greater and apparent use of social media as a platform for the organisation in crisis to reach out to its stakeholders.This preliminary paper studies the MH370 crisis in light of Coombs [1] Situational Crisis Communication Theory (SCCT).It aims to discuss the suitability of the CRS applied by Malaysia Airlines System (MAS) with the crisis type/s that was/were experienced by the organisation. Hence, the need for this paper to investigate the crisis type/s of MH370 and examines the CRS applied by MAS by content analysing media statements that were disseminated directly to the organisation’s stakeholders on Facebook during the first day of the crisis. Results ultimately show an interesting analysis to the crisis type of MH370, and the suitability of the CRS applied by MAS for that matter.